2002
DOI: 10.1139/w02-057
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of several genes encoding putative reductive dehalogenases inDesulfitobacterium hafniense/frappieriandDehalococcoides ethenogenes

Abstract: Desulfitobacterium frappieri PCP-1 has the capacity to dehalogenate several halogenated aromatic compounds by reductive dehalogenation, however, the genes encoding the enzymes involved in such processes have not yet been identified. Using a degenerate oligonucleotide corresponding to a conserved sequence of CprA/PceA reductive dehalogenases, a cprA-like gene fragment was amplified by PCR from this bacterial strain. A Desulfitobacterium frappieri PCP-1 cosmid library was screened with the PCR product, allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
41
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…and to identify RDase genes implicated in VC reductive dechlorination. Multiple alignments of full-length protein and DNA sequences of TceA (GenBank accession numbers AAN85590, AAN85588, and AAF73916A) and putative RDase genes identified in the genome of D. ethenogenes strain 195 (35) were constructed by using ClustalW and ClustalX (32). Conserved amino acid sequences were identified and used to design degenerate PCR primers (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…and to identify RDase genes implicated in VC reductive dechlorination. Multiple alignments of full-length protein and DNA sequences of TceA (GenBank accession numbers AAN85590, AAN85588, and AAF73916A) and putative RDase genes identified in the genome of D. ethenogenes strain 195 (35) were constructed by using ClustalW and ClustalX (32). Conserved amino acid sequences were identified and used to design degenerate PCR primers (Fig.…”
mentioning
confidence: 99%
“…A comparison of the translated amino acid sequence BvcA with putative RDases found on other Dehalococcoides sp. genomes (13,35) showed that sequence identity did not exceed 39% at the protein level. These findings indicate that bvcA is a unique gene not present in other described Dehalococcoides isolates.…”
mentioning
confidence: 99%
“…Access to whole-genome sequence data for D. ethenogenes strain 195 (http://www.tigr.org/tdb/mdb/mdbinprogress.html) allowed for a systematic screening for dehalogenase sequences (48). Besides the TCE dehalogenase-encoding tceA gene, 17 different reductive-dehalogenase-homologous (RDH) genes were found in strain 195, and all share the above-described features characteristic of dehalogenases (44,48).…”
mentioning
confidence: 99%
“…Besides the TCE dehalogenase-encoding tceA gene, 17 different reductive-dehalogenase-homologous (RDH) genes were found in strain 195, and all share the above-described features characteristic of dehalogenases (44,48). Hence, it was hypothesized that the genomes of Dehalococcoides populations contain multiple RDH genes, corresponding to the individual range of chlorinated electron acceptors used by individual strains.…”
mentioning
confidence: 99%
“…The low G ϩ C, Gram-positive bacterium D. dehalogenans, from which the protein studied here originates, can utilize hydroxylated polychlorinated biphenyls (10), and the Desulfitobacterium chlororespirans dehalogenase can use hydroxy-polychlorinated biphenyls as substrates (11). Multiple gene clusters encoding reductive dehalogenases have been detected in the genomes of dehalorespiring microbes, including 17 potential dehalogenases in Dehalococcoides ethenogenes (12). Some of the proteins involved in dehalorespiration are encoded in the cpr (chlorophenol reduction) gene cluster, which includes the reductive dehalogenase (cprA), its membrane anchor (cprB), several proposed chaperonins (cprT, -Z, -E, and -D), and two putative regulatory proteins (cprC and cprK) that are organized into four transcriptional units encoding cprT, cprBA, cprZE, and cprBACD (13).…”
mentioning
confidence: 99%